Gen Z Consumer Behavior and Food Waste in All-You-Can-Eat Restaurants: Uncovering the Value-Waste Paradox and Sustainable Dining Interventions in Indonesia - Nila Krisnawati; Evita Kho (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Generation Z (Gen Z), born between 1997 and 2012, is widely characterized as a socially and environmentally conscious cohort. However, a paradox emerges when their sustainability values encounter the structural incentives of All-You-Can-Eat (AYCE) dining, a fixed-price model that economically rewards overconsumption and generates significant plate waste. Objective: This study aims to understand Gen Z’s food selection behaviour in AYCE settings by identifying the factors that drive such behaviour, exploring their emotional and moral attitudes toward food waste, and identifying effective behavioural interventions that can promote more responsible dining choices in buffet environments. Methods: A qualitative research design was employed using in-depth semi-structured interviews with 20 Gen Z participants in Indonesia aged 18–24 years. Data were analyzed using reflexive thematic analysis facilitated by NVivo 12 software, from which ten core themes emerged. Results: The NVivo analysis yielded ten core themes organized under two overarching constructs. First, the Value-Waste Paradox: participants systematically prioritized high-cost items, such as meat and seafood, while neglecting lower-perceived-value foods, such as vegetables—a value-maximizing behaviour that frequently resulted in plate waste. Second, the Guilt-Inaction Gap: although most participants expressed guilt and regret over wasted food, this emotional awareness rarely translated into behavioural changes during the meal itself. Nevertheless, participants demonstrated receptiveness to dual-pronged interventions, including punitive measures (e.g., fines for excessive leftovers) and gamified incentives (e.g., digital badges or discounts for clean plates). Conclusion: This study contributes to consumer behaviour and sustainability theory by empirically grounding two novel constructs: the Value-Waste Paradox, wherein economic rationality in fixed-price settings systematically overrides pro-environmental intentions, and the Guilt-Inaction Gap, wherein emotional awareness of waste fails to motivate behavioural change under AYCE’s sunk-cost dynamics. The findings offer actionable insights for restaurant managers and policymakers seeking to reduce food waste among Gen Z consumers through structural redesign rather than attitude change alone.